2020
DOI: 10.1152/ajplung.00389.2019
|View full text |Cite
|
Sign up to set email alerts
|

Platelet glycolytic metabolism correlates with hemodynamic severity in pulmonary arterial hypertension

Abstract: Group 1 pulmonary hypertension (PH), i.e., pulmonary arterial hypertension (PAH), is associated with a metabolic shift favoring glycolysis in cells comprising the lung vasculature as well as skeletal muscle and right heart. We sought to determine whether this metabolic switch is also detectable in circulating platelets from PAH patients. We used Seahorse Extracellular Flux to measure bioenergetics in platelets isolated from group 1 PH (PAH), group 2 PH, patients with dyspnea and normal pulmonary artery pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Some reports 8 elucidate that aerobic glycolysis mediates PASMCs hyperproliferation and resistance to apoptosis causing pulmonary arterial remodeling. Although other studies have confirmed that platelet is activated in both patients with PAH and murine models, 13,[35][36][37][38][39] there has been little attention towards the platelet effect on PASMCs aerobic glycolysis. Previous studies have reported that the levels of TGF-β isoforms increase and the TGF-β-dependent signaling enhances in both familial PAH and IPAH (idiopathic pulmonary arterial hypertension) patients' lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports 8 elucidate that aerobic glycolysis mediates PASMCs hyperproliferation and resistance to apoptosis causing pulmonary arterial remodeling. Although other studies have confirmed that platelet is activated in both patients with PAH and murine models, 13,[35][36][37][38][39] there has been little attention towards the platelet effect on PASMCs aerobic glycolysis. Previous studies have reported that the levels of TGF-β isoforms increase and the TGF-β-dependent signaling enhances in both familial PAH and IPAH (idiopathic pulmonary arterial hypertension) patients' lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is related to inducing pulmonary vascular remodeling and the process of lipid mediators in PAH pathophysiology ( Voelkel and Tuder, 2000 ). Platelet glycolytic metabolism correlates with hemodynamic severity and aberrant lung vasculature in pulmonary arterial hypertension ( McDowell et al, 2020 ). Finally, we have verified the expression level of the 10 screened hub genes in lung tissue of rats with PAH, and the validation results are highly consistent with our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is defined by increased basal glycolysis and reduced glycolytic reserve. 28 , 29 Interestingly, platelet bioenergetics has been correlated with haemodynamic parameters, including mean pulmonary artery pressure and pulmonary vascular resistance (PVR). 28 These quantitative and qualitative platelet abnormalities highlight the potential role of platelets in the pathobiology of PAH and the importance of further studies in this field.…”
Section: Platelets In Pahmentioning
confidence: 99%